STRATEGI PENGEMBANGAN USAHATANI BUAH NAGA MERAH (Hylocereus polyrhizus) DI KABUPATEN OGAN KOMERING ULU (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2017)
This research was conducted to know the internal factors (strengths and weaknesses) and external factors (opportunities and threats) in the development of red dragon fruit farming. And analyzing the strategy of developing red dragon fruit farm in Ogan Komering Ulu Regency. Sampling technique using purposive method. The results showed that Internal Factors (Strength) on red dragon fruit farming is 1) The quality of red dragon fruit is good. 2) Easy cultivation and small risk. And Internal Factors (Weakness) on red dragon fruit farming is 1) The marketing of red aga is still lacking. 2) Knowledge of the cultivation of red dragon fruit is low. 3) Large initial capital. 4) Less workforce. External Factors (Opportunities) on red dragon fruit farm is 1) The production facilities are easy to obtain. 2) The demand for red dragon fruit is increasing. 3) Opportunities open wide business. And External Factors (Threat) on red dragon fruit farming is 1) Competition price of fellow red dragon fruit from outside Baturaja. 2) There has been no government attention to the development of red dragon fruit farming system. 3) There is no counseling to the red dragon fruit farmers. Alternative strategy matrix SWOT Strategy Development of Red Dragon Farming in Ogan Komering Ulu Regency is S-O Strategy 1) Utilizing existing production facilities to improve red dragon fruit yield. 2) Applying good and correct cultivation to increase the income of red dragon fruit farmers. W-O Strategy 1) Cooperate with red dragon fruit traders in order to improve marketing. 2) Optimization of training on cultivation of dragon fruit as well as cooperation with local communities in order to maintain harmony and increase employment opportunities to take advantage of existing business opportunities. Strategy S-T 1) Maintaining product quality and quality of red dragon fruit in order to increase sales of products that can benefit farmers. 2) Applying good and correct cultivation to develop red dragon fruit farming. W-T Strategy 1) Improving the quality of farmers' technical and non technical resources to maximize and maintain the constipation and competitiveness of red dragon fruit production. 2) Establish cooperation with the surrounding community in order to maintain harmony and increase employment opportunities.